Urethral Leiomyoma: A Rare Clinical Entity - Ng Beng Kwang; Aruku Naidu; Azyani Yahaya; Lim Pei Shan (Case Reports in Surgery)
Extrauterine leiomyomas are encountered occasionally, which can pose a diagnostic dilemma and challenge to the gynaecologist. We report a rare case of urethral leiomyoma. A 31-year-old woman with history of primary subfertility presented with mass at her urethral meatus and lower urinary tract symptoms. She underwent examination under anaesthesia and excision of the urethral mass. Histopathological examination confirmed leiomyoma. Diagnosis and management of this common growth situated at a rare location were reviewed and discussed.